2022
DOI: 10.3389/ijph.2022.1605045
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Education and Lifestyle Factors on Disability-Free Life Expectancy From Mid-Life to Older Age: A Multi-Cohort Study

Abstract: Objectives: Low education and unhealthy lifestyle factors such as obesity, smoking, and no exercise are modifiable risk factors for disability and premature mortality. We aimed to estimate the individual and joint impact of these factors on disability-free life expectancy (DFLE) and total life expectancy (TLE).Methods: Data (n = 22,304) were from two birth cohorts (1921–26 and 1946–51) of the Australian Longitudinal Study on Women’s Health and linked National Death Index between 1996 and 2016. Discrete-time mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 49 publications
1
1
0
Order By: Relevance
“…The results from the Health and Retirement Study further demonstrated that higher education was associated with compression of mortality and disability 65 . A multicohort study in Australia found that education modified the effect of lifestyle on DFLE 66 . The current study showed a graded relationship between education and DLE (Figure 2).…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…The results from the Health and Retirement Study further demonstrated that higher education was associated with compression of mortality and disability 65 . A multicohort study in Australia found that education modified the effect of lifestyle on DFLE 66 . The current study showed a graded relationship between education and DLE (Figure 2).…”
Section: Discussionsupporting
confidence: 62%
“…65 A multicohort study in Australia found that education modified the effect of lifestyle on DFLE. 66 The current study showed a graded relationship between education and DLE (Figure 2). Both men and women with high WPA had lower education levels (Table 1).…”
Section: Discussionmentioning
confidence: 51%
“…Having more than one SCAD was predictive of increased work impacts, including stopping work and/or reducing work hours, and increased likelihood of ceasing a favorite sport or exercise. Given that engagement in work and maintenance of exercise both contribute to physical and mental health and wellbeing during midlife [56,57], these additional risks for people who have experienced SCAD recurrence are notable. These findings point to the additional loss of autonomy, control and choice associated with SCAD recurrence, highlighting SCAD recurrence as a particularly stressful experience [44].…”
Section: Plos Onementioning
confidence: 99%
“…The results of the data are listed in Figure 4. Affiliate Charts [19], [20], [21], [22], [23]. The round diagram in Figure 5.…”
Section: Figure 3 Authors Name Chartsmentioning
confidence: 99%